CHARCTERISTICS OF NEW BUILDINGS IN THE IMPACT AREA OF A LARGE CITY - Anna Sikora (Journal of Civil Engineering, Environment and Architecture, 2022)
The existence of many field estates, despite their apparent order, from the landscape point of view is chaotic, incoherent and inefficient in terms of communication. The article attempts to create a typology of the most characteristic layouts of housing estates and to indicate the main factors influencing the formation of building complexes. The subject of the study is the analysis of the specificity of the spatial development of suburban zones in three cities: Rzeszów, Poznań and Warsaw. The aim of the analysis is to show the similarities and differences in selected areas. The implementation effect is the recognition of the nature of the buildings spreading outside the city’s territory. Determining the typology of buildings that can be located in specific areas may also help in practice of issuing decisions on development conditions. The catalogue of possible solutions, together with the analysis of the produced communication systems, will allow to forecast the spatial shape of future investments and, consequently, to optimize the provisions limiting pathological solutions.